The Early Repolarization Pattern: A Consensus Paper - Macfarlane, Peter W; Antzelevitch, Charles; Haissaguerre, Michel; Huikuri, Heikki V; Potse, Mark; Rosso, Raphael; Sacher, Frederic; Tikkanen, Jani T; Wellens, Hein; Yan, Gan-Xin (Journal of the American College of Cardiology, 2015)
The term early repolarization has been in use for more than 50 years. This electrocardiographic pattern was considered benign until 2008, when it was linked to sudden cardiac arrest due to idiopathic ventricular fibrillation. Much confusion over the definition of early repolarization followed. Thus, the objective of this paper was to prepare an agreed definition to facilitate future research in this area. The different definitions of the early repolarization pattern were reviewed to delineate the electrocardiographic measures to be used when defining this pattern. An agreed definition has been established, which requires the peak of an end-QRS notch and/or the onset of an end-QRS slur as a measure, denoted Jp, to be determined when an interpretation of early repolarization is being considered. One condition for early repolarization to be present is Jp ≥0.1 mV, while ST-segment elevation is not a required criterion.